Polymer composition, molded body, and nerve regeneration guide tube

A polymer composition of polylactic acid and dilactide/ε-caprolactone copolymer with controlled R value and crystallization rate addresses the issues of hardness and moldability in polylactic acid, providing flexible and strong materials for medical applications like nerve regeneration guiding tubes.

JP7619042B2Active Publication Date: 2025-01-22TORAY INDUSTRIES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020532837
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-30
Filing Date
2020-05-26
Publication Date
2025-01-22
Estimated Expiration
2040-05-26

AI Technical Summary

Technical Problem

Polylactic acid and polyglycolic acid-based polymers exhibit high crystallinity, high Young's modulus, and hard properties, leading to poor softness and biological conformability, which can cause tissue damage or ejection accidents when used in medical applications, and existing resin compositions have high Young's modulus, requiring materials with low Young's modulus for better moldability.

Method used

A polymer composition combining polylactic acid with a dilactide/ε-caprolactone copolymer, where the copolymer has an R value of 0.45 to 0.99 and a crystallization rate of less than 14%, with a specific mass ratio of 20 to 40% polylactic acid, to achieve low Young's modulus, high tensile strength, and excellent flexibility.

Benefits of technology

The composition achieves a balance of low Young's modulus, high tensile strength, and flexibility, suitable for medical applications such as nerve regeneration guiding tubes, with properties comparable to living tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619042000002
    Figure 0007619042000002
  • Figure 0007619042000003
    Figure 0007619042000003
  • Figure 0007619042000004
    Figure 0007619042000004
Patent Text Reader

Abstract

The purpose of the present invention is to provide a polymer composition which has low Young's modulus, high tensile strength and excellent flexibility. The present invention is a polymer composition which contains a polylactic acid and a dilactide / ε-caprolactone copolymer, wherein 20-40% by mass of the polylactic acid is contained relative to a total of 100% by mass of the polylactic acid and the dilactide / ε-caprolactone copolymer; and the dilactide / ε-caprolactone copolymer satisfies the requirements (1) and (2) described below. (1) The R value represented by the formula below is from 0.45 to 0.99 (inclusive). R = (AB) / (2(A)(B)) × 100 In the formula, (A) is the molar fraction (%) of dilactide residues in the dilactide / ε-caprolactone copolymer; (B) is the molar fraction (%) of ε-caprolactone residues in the dilactide / ε-caprolactone copolymer; and (AB) is the molar fraction (%) of structures, in which a dilactide residue and an ε-caprolactone residue are adjacent to each other (A-B and B-A), in the dilactide / ε-caprolactone copolymer. (2) At least either of the dilactide residues or the ε-caprolactone residues have a degree of crystallization of less than 14%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymer composition containing polylactic acid and a dilactide / ε-caprolactone copolymer, and a molded article thereof. [Background technology]

[0002] Polyesters produced from ester bond-forming monomers, such as polylactic acid, polyglycolic acid, polycaprolactone, and copolymers thereof, have attracted attention as biodegradable or bioabsorbable polymers and are used in a wide range of applications, for example, as medical materials such as sutures, sustained release materials for medicines, agricultural chemicals, fertilizers, etc. Furthermore, they are expected to be used as packaging materials for containers, films, etc. as general-purpose biodegradable plastics.

[0003] However, biodegradable polyesters and bioabsorbable polyesters produced from ester bond-forming monomers are generally brittle, and therefore attempts have been made to develop various copolymers with the aim of improving the mechanical properties to obtain biodegradable polymers with sufficient strength and moldability for practical use.

[0004] For example, a polyester copolymer has been proposed as a biodegradable / bioabsorbable polymer with a low Young's modulus and high tensile strength, which is composed mainly of residues of two types of ester bond-forming monomers ("monomer A" and "monomer B"), in which the R value represented by the following formula is 0.45 or more and 0.99 or less, and in which the crystallization rate of at least one of the monomer A residues or monomer B residues is less than 14% (see, for example, Patent Document 1). R = [AB] / (2[A][B]) × 100 [A]: Molar fraction (%) of monomer A residues in the polyester copolymer [B]: Molar fraction (%) of monomer B residues in the polyester copolymer [AB]: The mole fraction (%) of the structure in which monomer A residues and monomer B residues are adjacent to each other in the polyester copolymer.

[0005] Attempts have also been made to improve mechanical properties by blending biodegradable polymers. For example, as compositions with improved strength, flexibility, elongation, toughness, etc., biodegradable polymer blends (see, for example, Patent Document 2) that contain at least one synthetic hard biodegradable polymer and at least one synthetic soft biodegradable polymer, have higher strength and / or elongation than the hard or soft biodegradable polymers themselves, and are suitable for forming into at least one sheet or film, and resin compositions (see, for example, Patent Document 3) that contain polylactic acid, L-lactide / ε-caprolactone copolymer, and a filler have been proposed. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2019 / 35857 [Patent Document 2] JP 2008-255349 A [Patent Document 3] JP 2017-179234 A Summary of the Invention [Problem to be solved by the invention]

[0007] In general, polylactic acid and polyglycolic acid are known to have high crystallinity, high Young's modulus, and hardness. However, molded bodies of these polymers lack flexibility and are inferior to the biocompatible properties required for medical materials. In addition, it has been reported that because of their hardness, they can damage surrounding tissues or cause extrusion accidents when embedded in the body.

[0008] Therefore, copolymerization of these polymers with polycaprolactone has been studied to impart flexibility. The multi-gradient polymer described in Patent Document 1 has a low Young's modulus and high tensile strength, and therefore is easy to mold and difficult to break, making it suitable for use as a filler or coating material. On the other hand, in applications such as supports and fixed substrates, in addition to these properties, it is required that the polymer be easily elastically deformed, i.e., have excellent flexibility.

[0009] Moreover, the resin compositions described in Patent Documents 2 and 3 have a high Young's modulus, and from the viewpoint of molding processability, materials having a low Young's modulus are desired.

[0010] In view of the above problems, an object of the present invention is to provide a polymer composition having a low Young's modulus, high tensile strength and excellent flexibility. [Means for solving the problem]

[0011] The present invention relates to a polymer composition containing polylactic acid and a dilactide / ε-caprolactone copolymer, the polylactic acid being contained in an amount of 20 to 40% by mass relative to 100% by mass in total of the polylactic acid and the dilactide / ε-caprolactone copolymer, and the dilactide / ε-caprolactone copolymer satisfying the following (1) and (2): (1) The R value represented by the following formula is 0.45 or more and 0.99 or less. R = [AB] / (2[A][B]) × 100 Here, [A]: Molar fraction (%) of dilactide residues in dilactide / ε-caprolactone copolymer [B]: Molar fraction (%) of ε-caprolactone residues in the dilactide / ε-caprolactone copolymer [AB]: The mole fraction (%) of structures (AB and BA) in which dilactide residues and ε-caprolactone residues are adjacent to each other in the dilactide / ε-caprolactone copolymer. (2) The crystallinity of at least one of the dilactide residues and the ε-caprolactone residues is less than 14%.

[0012] The present invention also relates to a molded article comprising the polymer composition of the present invention.

[0013] The present invention also relates to a nerve regeneration-inducing tube, at least in part, using the polymer composition of the present invention. Effect of the Invention

[0014] According to the present invention, a polymer composition having a low Young's modulus, high tensile strength and excellent flexibility can be obtained. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a graph showing the elongation-stress curve of the polymer composition obtained in Example 1. [Diagram 2] FIG. 2 is a graph showing the elongation-stress curve of the polymer obtained in Comparative Example 1. [Diagram 3] FIG. 3 is a graph showing the elongation-stress curve of the polymer composition obtained in Comparative Example 2. [Figure 4] FIG. 4 is a graph showing the elongation-stress curve of the polymer composition obtained in Comparative Example 3. [Diagram 5] FIG. 5 is a graph showing the elongation-stress curve of the polymer obtained in Comparative Example 4. [Figure 6] FIG. 6 is a graph showing the elongation-stress curve of the polymer composition obtained in Example 2. [Figure 7] FIG. 7 is a graph showing the elongation-stress curve of the polymer composition obtained in Example 3. [Figure 8] FIG. 8 is a graph showing the elongation-stress curve of the polymer composition obtained in Example 4. [Figure 9] FIG. 9 is a graph showing the elongation-stress curve of the polymer obtained in Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Polylactic acid> The polylactic acid in the polymer composition of the present invention is a polymer formed by polymerizing lactic acid through ester bonds. The polylactic acid may be a copolymer containing components other than lactic acid, but the molar fraction of lactic acid in the polylactic acid is preferably 80% or more, more preferably 90% or more, and even more preferably 100%, so that the crystallinity of lactic acid is high. In addition, there are two types of lactic acid, L-form and D-form, and in medical applications, from the viewpoint of biocompatibility, L - Homopolymers of lactic acid are preferred.

[0017] The weight average molecular weight of polylactic acid is preferably 60,000 or more from the viewpoint of preventing the molecular chain from unraveling and further improving flexibility. Furthermore, from the viewpoint of further improving tensile strength, it is more preferably 110,000 or more. On the other hand, the weight average molecular weight of polylactic acid is preferably 200,000 or less so that the Young's modulus of the polymer composition does not increase due to excessive crystallization. Here, the weight average molecular weight of polylactic acid refers to a polystyrene equivalent value and can be measured by gel permeation chromatography (GP).

[0018] <Production method of polylactic acid> Polylactic acid is L -Lactic acid, D Polylactic acid can be obtained by polymerizing or copolymerizing lactic acid such as -lactic acid. Polylactic acid can be synthesized, for example, by ring-opening polymerization of dilactide. L An example of a method for synthesizing polylactic acid using .beta.-dilactide is described below.

[0019] first, L -Dilactide and a co-initiator, such as lauryl alcohol, are collected in a separable flask.

[0020] Next, a catalyst is added under a nitrogen atmosphere, and the raw materials are stirred while being heated to dissolve or melt uniformly. Examples of the catalyst include tin(II) octylate. The heating temperature is preferably from the viewpoint of dissolving the raw materials uniformly, and is preferably 140° C. or less from the viewpoint of suppressing the volatilization of the raw materials. The stirring speed is preferably 80 rpm or more and 200 rpm or less. The heating time is preferably 10 minutes or more and 60 minutes or less.

[0021] The mixture is further heated and allowed to stand for 1 hour, and then the temperature is lowered and allowed to stand for another hour. The heating temperature is preferably 150°C or higher and 180°C or lower. The standing time is preferably 2 hours or shorter from the viewpoint of suppressing excessive polymerization. The temperature at which the mixture is lowered is preferably 120°C or higher from the viewpoint of proceeding with the reaction. L From the viewpoint of suppressing the volatilization of dilactide, the temperature is preferably 140° C. or less. The standing time is preferably 24 hours or less.

[0022] After that, the flask was evacuated while maintaining the temperature, and the unreacted L -dilactide is removed. Finally, the reaction mixture is dissolved in chloroform or the like, and the solution is dropped into stirred methanol to precipitate polylactic acid. The stirring speed of methanol is preferably 200 rpm or more and 300 rpm or less. It is preferable to dry the resulting polylactic acid to remove the solvent in the polylactic acid. The drying time is preferably 12 hours or more.

[0023] <Dilactide / ε-caprolactone copolymer> The dilactide / ε-caprolactone copolymer in the polymer composition of the present invention satisfies the following (1) and (2).

[0024] (1) The R value represented by the following formula is 0.45 or more and 0.99 or less. R = [AB] / (2[A][B]) × 100 Here, [A]: Molar fraction (%) of dilactide residues in dilactide / ε-caprolactone copolymer [B]: Molar fraction (%) of ε-caprolactone residues in the dilactide / ε-caprolactone copolymer [AB]: The mole fraction (%) of structures (AB and BA) in which dilactide residues and ε-caprolactone residues are adjacent to each other in the dilactide / ε-caprolactone copolymer.

[0025] The R value can be determined by quantifying the ratio of the combinations of two adjacent monomers (AA, BB, AB, BA) using nuclear magnetic resonance (NMR) measurements. Specifically, a dilactide / ε-caprolactone copolymer is dissolved in deuterated chloroform, 1 The ratios of dilactide residues and ε-caprolactone residues in the dilactide / ε-caprolactone copolymer are calculated by H-NMR analysis. 1 Using the H homospin decoupling method, the methine group of dilactide (around 5.10 ppm), the α-methylene group of ε-caprolactone (around 2.35 ppm), and the ε-methylene group (around 4.10 ppm) are separated by the signal derived from the adjacent monomer residue of lactide or ε-caprolactone, and the peak area of ​​each is quantified. The [AB] in formula 1 is calculated from the area ratio of each, and the R value is calculated. Here, [AB] is the molar fraction (%) of the structure in which the dilactide residue and the ε-caprolactone residue are adjacent, specifically, the ratio of the number of AB and BA to the total number of AA, AB, BA, and BB.

[0026] The R value is used as an index showing the randomness of the arrangement of monomer residues in a dilactide / ε-caprolactone copolymer. For example, a random copolymer in which the monomer arrangement is completely random has an R value of 1. When the R value is 0.45 or more, the copolymer has low crystallinity and excellent flexibility. An R value of 0.50 or more is preferable. On the other hand, when the R value is 0.99 or less, the adhesiveness can be suppressed. An R value of 0.80 or less is preferable.

[0027] (2) The crystallinity of at least one of the dilactide residues and the ε-caprolactone residues is less than 14%.

[0028] If the crystallization rate is less than 14%, the Young's modulus can be suppressed to obtain flexibility, thereby obtaining a polyester copolymer suitable for medical materials and elastomer applications. In the present invention, the crystallization rate of the dilactide residue is preferably less than 14%, and more preferably 10% or less.

[0029] The crystallization rate of the monomer residue referred to here is the ratio of the heat of fusion per unit mass of the monomer residue in the dilactide / ε-caprolactone copolymer to the product of the heat of fusion per unit mass of a homopolymer consisting of only a certain monomer residue and the mass fraction of the monomer residue in the dilactide / ε-caprolactone copolymer. In other words, the crystallization rate of the dilactide residue is the ratio of the heat of fusion per unit mass of the dilactide residue in the dilactide / ε-caprolactone copolymer to the product of the heat of fusion per unit mass of a homopolymer consisting of only dilactide and the mass fraction of the dilactide residue in the dilactide / ε-caprolactone copolymer. The crystallization rates of the dilactide residue and ε-caprolactone residue indicate the ratio of the dilactide residue or ε-caprolactone residue in the dilactide / ε-caprolactone copolymer that form a crystalline structure. Here, the crystallization rate can be measured by the DSC method using a differential scanning calorimeter.

[0030] The dilactide / ε-caprolactone copolymer may be linear or branched.

[0031] The weight average molecular weight of the dilactide / ε-caprolactone copolymer is preferably 60,000 or more, more preferably 100,000 or more, from the viewpoint of further reducing the Young's modulus of the polymer composition and further improving the tensile strength. On the other hand, the weight average molecular weight of the dilactide / ε-caprolactone copolymer is preferably 400,000 or less, from the viewpoint of the viscosity and solubility of the polymer composition described below. Here, the weight average molecular weight of the dilactide / ε-caprolactone copolymer refers to a polystyrene equivalent value, and can be measured by gel permeation chromatography (GPC).

[0032] In the present invention, the dilactide / ε-caprolactone copolymer preferably has a gradient structure in which dilactide residues and ε-caprolactone residues form a composition gradient in the skeleton.

[0033] A gradient structure that forms a composition gradient in the backbone refers to a structure in which the composition of monomer residues changes continuously from the polymerization initiation end to the polymerization termination end along the molecular chain. Schematically, for example, residue A and residue B are AAAAABAAABAABBABABBBBBABBBB They are lined up like this.

[0034] The dilactide / ε-caprolactone copolymer has a gradient structure in which the dilactide residues and the ε-caprolactone residues form a composition gradient in the skeleton, and this makes it possible to suppress the crystallinity and obtain flexibility compared to the case of having a block copolymer structure.

[0035] The randomness of the distribution of monomer residues constituting the dilactide / ε-caprolactone copolymer changes depending on the difference in the reactivity of the monomers during polymerization. That is, if the same monomer and the other monomer are bonded with the same probability after one of the dilactide and caprolactone monomers during polymerization, a random copolymer with completely randomly distributed monomer residues is obtained. However, if there is a tendency for one monomer to be bonded after the other monomer, a gradient copolymer with a biased distribution of monomer residues is obtained.

[0036] Here, the reactivity of dilactide and ε-caprolactone is significantly different as described in the literature (DW Grijpma et al. Polymer Bulletin 25, 335, 341), and the initial polymerization rate of dilactide is higher than that of ε-caprolactone. The initial polymerization rate of dilactide V A The reaction rate (%) was 3.6% / h, and the initial polymerization rate of ε-caprolactone V BThe rate of polymerization is 0.88% / h. When dilactide and ε-caprolactone are copolymerized, dilactide is likely to bond after dilactide. Therefore, a gradient structure is formed in which the ratio of dilactide units gradually decreases from the polymerization initiation terminal to the polymerization termination terminal.

[0037] That is, according to a copolymerization method in which dilactide and ε-caprolactone monomers are mixed and reacted, a dilactide / ε-caprolactone copolymer generally tends to form a gradient structure throughout the entire polymer skeleton.

[0038] Furthermore, in the present invention, the dilactide / ε-caprolactone copolymer preferably has a gradient structure in the macromer units, and has a structure in which two or more of the macromer units are linked together.

[0039] Here, the term "macromer" refers to a high molecular weight compound having a polymerizable functional group, and in a polymer, the macromer unit forms a part of the polymer skeleton. In a structure in which two or more macromer units having a gradient structure are linked together, for example, (AAABAABBABBB)·(AAABAABBABBB) They are lined up like this.

[0040] Hereinafter, a macromer having a gradient structure is also referred to as a "gradient macromer," and a unit of a gradient macromer in a polymer is also referred to as a "gradient macromer unit."

[0041] By having a structure in which two or more gradient macromer units are linked, even if the degree of polymerization is increased, it is possible to effectively obtain a dilactide / ε-caprolactone copolymer with controlled randomness as in the above-mentioned (1), and also to effectively obtain a dilactide / ε-caprolactone copolymer with reduced crystallinity as in the above-mentioned (2).Accordingly, such a preferred embodiment makes it possible to effectively obtain a polymer composition with a low Young's modulus and high tensile strength.

[0042] From the viewpoint of further improving the tensile strength, the number of macromer units in the structure in which the macromer units are linked is preferably 3 or more, and more preferably 6 or more. On the other hand, from the viewpoint of appropriately suppressing the viscosity and improving the handleability, the number of linked macromer units is preferably 20 or less.

[0043] Hereinafter, a structure in which two or more gradient macromer units are linked will be referred to as a "multi-gradient structure," and a copolymer having a multi-gradient structure will be referred to as a "multi-gradient copolymer."

[0044] In the present invention, the maximum point stress of the dilactide / ε-caprolactone copolymer film is preferably 5 MPa to 30 MPa, which is the same as that of biological tissue, and the Young's modulus of the dilactide / ε-caprolactone copolymer is preferably 1.0 MPa to 6.3 MPa, which is the same as that of biological tissue.

[0045] Here, the maximum point stress and Young's modulus when the dilactide / ε-caprolactone copolymer is made into a film can be measured according to the method specified in JIS K6251 (2017). Specifically, the dilactide / ε-caprolactone copolymer is dried under reduced pressure, and the solution obtained by dissolving the copolymer in chloroform to a concentration of 5% by mass is transferred onto a "Teflon" (registered trademark) petri dish and dried at normal pressure and room temperature for one day and night. The polymer film obtained by drying under reduced pressure and having a thickness of 0.1 mm is cut into strips (30 mm x 5 mm) and measured using a small tabletop testing machine EZ-LX (manufactured by Shimadzu Corporation). Initial length: 10mm, Tensile speed: 500mm / min, Load cell: 50N A tensile test is carried out under the above conditions, and the maximum stress and Young's modulus are measured. Each measurement is carried out three times, and the number average values ​​are calculated, so that the maximum stress and Young's modulus of the dilactide / ε-caprolactone copolymer can be obtained.

[0046] The maximum stress and Young's modulus of the dilactide / ε-caprolactone copolymer can be effectively controlled within the above-mentioned ranges by forming a structure in which two or more of the above-mentioned gradient macromer units are linked together by a production method having a multi-formation step described below.

[0047] <Production method of dilactide / ε-caprolactone copolymer> Dilactide / ε-caprolactone copolymer is an example. a macromer synthesis step of blending and polymerizing dilactide and ε-caprolactone such that the sum of dilactide residues and ε-caprolactone residues is 50 mol % or more of the total residues and the dilactide residues and ε-caprolactone residues each are 20 mol % or more of the total residues at the completion of polymerization; a multi-polymerization step of linking the macromers obtained in the macromer synthesis step to each other or by further adding dilactide and ε-caprolactone to the macromer solution obtained in the macromer synthesis step; The present invention can be produced by a production method having the steps of:

[0048] [Macromer synthesis process] In the macromer synthesis step, dilactide and ε-caprolactone are mixed and polymerized so that the sum of dilactide residues and ε-caprolactone residues is theoretically 50 mol % or more of the total residues at the end of polymerization, and dilactide residues and ε-caprolactone residues are each 20 mol % or more of the total residues. This produces a dilactide / ε-caprolactone copolymer having dilactide residues and ε-caprolactone residues as main structural units, but since this production method further includes a multi-production step described later, in this specification, the dilactide / ε-caprolactone copolymer obtained by this step is referred to as a "macromer."

[0049] In this step, due to the difference in initial polymerization rate between dilactide and ε-caprolactone, a macromer having a gradient structure in which dilactide residues and ε-caprolactone residues form a composition gradient in the skeleton is obtained.

[0050] In order to realize such a gradient structure in the macromer synthesis step, it is desirable to synthesize the macromer by a polymerization reaction that occurs in one direction from the initiation terminal. Preferred examples of such a synthesis reaction include ring-opening polymerization and living polymerization.

[0051] An example of a method for synthesizing lactide / caprolactone macromer will now be described in more detail. First, dilactide, ε-caprolactone, and a catalyst are placed in a reaction vessel equipped with a stirrer, and stirred while heating under a nitrogen stream. In order to remove moisture from inside the reaction vessel, it is preferable to heat and stir the reaction vessel under reduced pressure.

[0052] The stirrer is preferably one equipped with a propeller-type stirring blade, and the rotation speed of the stirring blade is preferably 50 rpm or more and 200 rpm or less.

[0053] The heating temperature of the polymerization reaction is preferably 100° C. or more and 250° C. or less. The reaction time of the polymerization reaction is preferably 3 hours or more, more preferably 5 hours or more, and even more preferably 7 hours or more, from the viewpoint of increasing the degree of polymerization. On the other hand, the reaction time of the polymerization reaction is preferably 24 hours or less, from the viewpoint of further improving productivity.

[0054] It is preferable that dilactide and ε-caprolactone are purified in advance to remove impurities before use.

[0055] Examples of the catalyst include tin octylate, antimony trifluoride, zinc powder, dibutyltin oxide, and tin oxalate. Examples of the method of adding the catalyst to the reaction system include adding the catalyst in a dispersed state in the raw materials when the raw materials are charged, and adding the catalyst in a dispersed state in the medium at the start of the pressure reduction or immediately before the start of heating in the above-mentioned method. From the viewpoint of shortening the reaction time and further improving the productivity, the amount of the catalyst used is preferably 0.01 parts by mass or more, more preferably 0.04 parts by mass or more, in terms of metal atoms, relative to 100 parts by mass of dilactide and ε-caprolactone in total. On the other hand, from the viewpoint of further reducing the amount of metal remaining in the dilactide / ε-caprolactone copolymer, the amount of the catalyst used is preferably 0.5 parts by mass or less, in terms of metal atoms, relative to the total amount of dilactide and ε-caprolactone.

[0056] When water is used as a co-initiator, it is preferred to carry out a co-catalysis reaction at about 90° C. prior to the polymerization reaction.

[0057] In order to facilitate the final production of a dilactide / ε-caprolactone copolymer satisfying the R value shown in (1) above, the macromer obtained in this step is one having an R value similar to that of the dilactide / ε-caprolactone copolymer described in (1) above, that is, one having the following formula: R value = [AB] / (2[A][B]) x 100 [A]: Molar fraction (%) of dilactide residues in the macromer [B]: Molar fraction (%) of ε-caprolactone residues in the macromer [AB]: Molar fraction (%) of structures (AB and BA) in which dilactide residues and ε-caprolactone residues are adjacent to each other in the macromer The R value represented by the following formula is preferably 0.45 or more and 0.99 or less, and more preferably 0.50 or more and 0.80 or less.

[0058] Similarly, in order to facilitate the final production of a dilactide / ε-caprolactone copolymer having the crystallization rate of the dilactide residue or ε-caprolactone residue shown in (2) above, the macromer obtained in this step preferably has the crystallization rate of the monomer residues described in (2) above, i.e., the crystallization rate of at least one of the dilactide residue or ε-caprolactone residue is less than 14%, more preferably 10% or less, even more preferably 5% or less, and most preferably 1% or less.

[0059] The weight-average molecular weight of the macromer synthesized in the macromer synthesis step is preferably 10,000 or more, more preferably 20,000 or more. In order to further reduce crystallinity and further improve flexibility, the weight-average molecular weight is preferably 150,000 or less, more preferably 100,000 or less.

[0060] [Multi-layering process] In the multi-forming step, the macromers obtained in the macromer synthesis step are linked together, or dilactide and caprolactone are added to the macromer solution obtained in the macromer synthesis step to form a multi-polymer. In this step, the macromers obtained in one macromer synthesis step may be linked together, or multiple macromers obtained in two or more macromer synthesis steps may be linked. Note that "multi-forming" means that, by any of these methods, a structure is formed in which multiple molecular chains having a gradient structure in which dilactide residues and caprolactone residues have a composition gradient in the skeleton are repeated.

[0061] The number of linked macromer units can be adjusted by the catalyst and reaction time used in the multi-polymerization step. When linking macromers together to form a multi-polymer, the number of macromer units can be determined by dividing the weight-average molecular weight of the final dilactide / ε-caprolactone copolymer by the weight-average molecular weight of the macromer.

[0062] The reaction temperature of the condensation reaction in the multi-polymerization step is preferably 20°C or higher from the viewpoint of efficiently proceeding with the condensation reaction. On the other hand, the reaction temperature of the condensation reaction is preferably 50°C or lower from the viewpoint of suppressing the evaporation of the solvent. Furthermore, the reaction time of the condensation reaction is preferably 15 hours or longer from the viewpoint of setting the number of macromer units to be multi-polymerized in the above-mentioned preferred range. On the other hand, the reaction time of the condensation reaction is preferably 24 hours or shorter from the viewpoint of narrowing the molecular weight distribution.

[0063] A linear dilactide / ε-caprolactone copolymer can be produced, for example, by binding one molecule of a similar gradient macromer to each end of a gradient macromer via the ends.

[0064] When the gradient macromer has a hydroxyl group and a carboxyl group at each end, the ends are condensed with a condensing agent to obtain a multi-polymerized dilactide / ε-caprolactone copolymer. Examples of the condensing agent include 4,4-dimethylaminopyridinium p-toluenesulfonate, N,N'-dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, and N,N'-carbonyldiimidazole. Two or more of these may be used.

[0065] Furthermore, when the polymerization reaction has a living nature, that is, when the polymerization reaction can be continuously initiated from the terminal of the polymer, multimerization can be achieved by repeatedly adding dilactide and ε-caprolactone to the gradient macromer solution after the polymerization reaction is completed.

[0066] Alternatively, gradient macromers may be multi-linked via a linker as long as it does not affect the mechanical properties of the polymer. In particular, by using a linker having multiple carboxyl groups and / or multiple hydroxyl groups, such as 2,2-bis(hydroxymethyl)propionic acid, it is possible to synthesize a branched polyester copolymer in which the linker is the branch point.

[0067] The dilactide / ε-caprolactone copolymer obtained by the above-mentioned production method is a copolymer having a structure in which two or more macromer units, in which didilactide residues and caprolactone residues have a composition gradient in the skeleton, are linked together, and this is a preferred embodiment of the dilactide / ε-caprolactone copolymer of the present invention.

[0068] <Polymer composition> The polymer composition of the present invention contains the above-mentioned polylactic acid and a dilactide / ε-caprolactone copolymer.

[0069] Dilactide / ε-caprolactone that satisfies the above (1) and (2) has a low crystallization rate, which reduces the Young's modulus and improves the tensile strength, but since the molecular chains are simply entangled, when stress is applied, the molecular chains are first deformed to relax the entanglements, making it difficult to generate elastic force and low flexibility in the initial stage of elongation. On the other hand, polylactic acid has high crystallinity and is thought to form a crystalline structure with the dilactide residues in the dilactide / ε-caprolactone copolymer. It is thought that such a crystalline structure forms crosslinks between the molecular chains of the dilactide / ε-caprolactone copolymer, which exerts rubber-like elasticity when stress is applied, improving flexibility.

[0070] The polymer composition of the present invention must contain 20 to 40% by mass of polylactic acid relative to 100% by mass of the total of polylactic acid and dilactide / ε-caprolactone copolymer. By making the content of polylactic acid 20% by mass or more, more preferably 30% by mass or more, it is possible to ensure sufficient crystal formation between polylactic acid and dilactide residues and improve flexibility. On the other hand, by making the content of polylactic acid 40% by mass or less, more preferably 35% by mass or less, it is possible to suppress excessive crystallization of polylactic acid and dilactide, and to suppress a high Young's modulus and a decrease in tensile strength.

[0071] When the polymer composition of the present invention is formed into a film, the maximum point stress is preferably 5 MPa to 30 MPa, which is the same as that of biological tissue, and the Young's modulus is preferably 1.0 MPa to 6.3 MPa, which is the same as that of biological tissue.

[0072] The maximum point stress and Young's modulus when the polymer composition is made into a film can be measured in accordance with the method specified in JIS K6251 (2017), and the details are the same as those for the dilactide / ε-caprolactone copolymer.

[0073] <Method of producing polymer composition> The polymer composition of the present invention can be obtained, for example, by stirring the above-mentioned polylactic acid and dilactide / ε-caprolactone copolymer in a molten state or in a solution state. From the viewpoint of suppressing thermal decomposition, it is preferable to stir in a solution state. More preferably, each polymer constituting the polymer composition is put together in the same solvent and dissolved while stirring, and then the solvent is removed by volatilization.

[0074] <Molded body made of polymer composition> The polymer composition of the present invention has excellent flexibility, and therefore can be used for molded articles that are frequently subjected to deformation. In particular, when used as a medical molded article, it can be transplanted into the body and, while retaining flexibility to follow the deformation of the body, can also serve as a support by showing resistance to deformations above a certain level. In particular, it is preferable to use the polymer composition as a nerve regeneration induction tube, which requires such a function. EXAMPLES

[0075] The present invention will be described below using specific examples. However, the present invention should not be interpreted as being limited to these examples. It should be understood that the present invention includes all technical ideas and specific embodiments that a person skilled in the art who comes into contact with the concept of the present invention would conceive and consider to be feasible.

[0076] [Measurement method] (1) Measurement of weight-average molecular weight by gel permeation chromatography (GPC) The dilactide / ε-caprolactone copolymer or polylactic acid to be measured was dissolved in chloroform and passed through a 0.45 μm syringe filter (DISMIC-13HP; manufactured by ADVANTEC) to remove impurities, etc. Then, the weight average molecular weight of the dilactide / ε-caprolactone copolymer and polylactic acid in terms of polystyrene was calculated by GPC measurement under the following conditions. Device name: Prominence (manufactured by Shimadzu Corporation) Mobile phase: Chloroform (for HPLC) (manufactured by Wako Pure Chemical Industries, Ltd.) Flow rate: 1mL / min Column: TSKgel GMHHR-M (φ7.8mm x 300mm; manufactured by Tosoh Corporation) Detector: A UV detector (254 nm) and an RI detector were operated, and the result from the RI detector was used to calculate the weight average molecular weight. Column and detector temperature: 35℃ Standard material: polystyrene.

[0077] (2) Measurement of crystallinity of dilactide residues by differential scanning calorimetry (DSC) The dilactide / ε-caprolactone copolymer to be measured was collected on an aluminum pan, and the heat of fusion was calculated by the DSC method under the following conditions using a differential scanning calorimeter (EXTAR 6000; manufactured by Seiko Instruments Inc.) The crystallization rate was calculated from the obtained heat of fusion using the following formula. Crystallization ratio = (heat of fusion per unit mass of dilactide residue of dilactide / ε-caprolactone copolymer) / {(heat of fusion per unit mass of homopolymer consisting of only dilactide residue) × (mass fraction of dilactide residue in dilactide / ε-caprolactone copolymer)} × 100 Device name: EXSTAR 6000 (Seiko Instruments Inc.) Temperature conditions: 25°C > 10°C / min heating to 250°C > 5 min heating at 250°C > 10°C / min cooling to -70°C > 10°C / min heating to 250°C > 5 min heating at 250°C > 100°C / min cooling to 25°C Standard material: aluminum.

[0078] (3) Measurement of the mole fraction (%) and R value of each residue by nuclear magnetic resonance (NMR) The dilactide / ε-caprolactone copolymer to be measured was dissolved in deuterated chloroform and analyzed under the following conditions. 1 The ratios of dilactide residues and caprolactone residues in the dilactide / ε-caprolactone copolymer were calculated by H-NMR. 1 Using the H homospin decoupling method, the methine group of lactide (around 5.10 ppm), the α-methylene group of caprolactone (around 2.35 ppm), and the ε-methylene group (around 4.10 ppm) were separated by the signal derived from the adjacent monomer residue of lactide or caprolactone, and the peak area of ​​each was quantified. The [AB] in formula 1 was calculated from the area ratio of each, and the R value was calculated. Here, [AB] is the molar fraction (%) of the structure in which the dilactide residue and the caprolactone residue are adjacent, specifically, the ratio of the number of AB and BA to the total number of AA, AB, BA, and BB. Device name: JNM-EX270 (manufactured by JEOL Ltd.) 1 H homospin decoupling irradiation position: 1.66 ppm Solvent: deuterated chloroform Measurement temperature: room temperature.

[0079] (4) Measurement of Young's modulus and maximum stress by tensile test The dilactide / ε-caprolactone copolymer or the polymer composition solution obtained in each of the Examples and Comparative Examples was dried under reduced pressure, and the solution obtained by dissolving the copolymer in chloroform to a concentration of 5% by weight was transferred onto a Teflon (registered trademark) petri dish and dried at room temperature under normal pressure for one day and night. This was then dried under reduced pressure to obtain a polymer composition film.

[0080] The obtained film (thickness about 0.1 mm) was cut into a rectangular shape (50 mm x 5 mm), and a tensile test was performed using EZ-LX (manufactured by Shimadzu Corporation) under the following conditions in accordance with JIS K6251 (2017), and the Young's modulus and maximum point stress were calculated. Note that the measurement conditions in JIS K6251 applied in the present invention are common to the 2017 version and the 2010 version. Device name: EZ-LX (manufactured by Shimadzu Corporation) Initial length: 10mm Tensile speed: 500mm / min Load cell: 50N Number of tests: 3.

[0081] (5) Evaluation of flexibility Using the polymer composition solutions or polymer solutions obtained in each of the Examples and Comparative Examples, a tensile test was performed by the method described in (4) above, and the elongation-stress curves obtained (FIGS. 1 to 9) were fitted with a linear equation (Y=aX, where Y is stress, X is elongation, and a is a constant) for the stress up to the elongation at which the maximum stress was observed. The coefficient of determination r was calculated from the average value of three tests. 2 Since flexibility is the ease of elastic deformation, the coefficient of determination r 2 The closer the value is to 1, the greater the elastic deformation, and a coefficient of determination of 0.85 or more is an indicator of excellent flexibility.

[0082] [Synthesis Example 1: Synthesis of dilactide / ε-caprolactone copolymer] 25g L18.3 mL of ε-caprolactone (manufactured by Wako Pure Chemical Industries, Ltd.) was collected as monomers in a separable flask. Under a nitrogen atmosphere, a solution of 0.05 parts by mass (in tin equivalent) of tin(II) octylate (manufactured by Wako Pure Chemical Industries, Ltd.) as a catalyst relative to 100 parts by mass of dilactide and ε-caprolactone in total was dissolved in 3.5 mL of toluene (ultra-dehydrated) (manufactured by Wako Pure Chemical Industries, Ltd.) and 227.4 mg of hydroxypivalic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) as a co-initiator was added, and the mixture was heated to 140°C and stirred at a stirring speed of 100 rpm for 12 hours to cause a copolymerization reaction, thereby obtaining a macromer solution.

[0083] To the obtained macromer solution, 1.67 g of 4,4-dimethylaminopyridinium p-toluenesulfonate (synthetic product) and 617.9 mg of 4,4-dimethylaminopyridine (manufactured by Wako Pure Chemical Industries, Ltd.) were added as catalysts. These were dissolved in 255 mL of dichloromethane (dehydrated) (manufactured by Wako Pure Chemical Industries, Ltd.) under a nitrogen atmosphere, and 5.76 g of dicyclohexylcarbodiimide (manufactured by Sigma-Aldrich Co.) was added as a condensation agent, followed by stirring at 25°C and a stirring speed of 100 rpm for 18 hours to carry out condensation polymerization.

[0084] To the reaction mixture, 3.0 mL of acetic acid (manufactured by Wako Pure Chemical Industries, Ltd.) and an amount of chloroform to give a dilactide / ε-caprolactone copolymer concentration of 15% by mass were added, and the mixture was stirred at 25°C and a stirring speed of 200 rpm for 2 hours. The reaction mixture was then added dropwise to 2.0 L of methanol while stirring at a stirring speed of 300 rpm to obtain a precipitate. The obtained precipitate was dried for 18 hours to obtain a dilactide / ε-caprolactone copolymer having a multi-gradient structure. The weight-average molecular weight of the obtained dilactide / ε-caprolactone copolymer was 240,000, the degree of polymerization of the macromonomer unit was 7.1, the crystallization rate of the dilactide residue was 0.0%, the crystallization rate of the ε-caprolactone residue was 0.0%, the molar fraction of the dilactide residue was 52%, the molar fraction of the ε-caprolactone residue was 48%, the molar fraction of the structure in which the dilactide residue and the ε-caprolactone residue were adjacent to each other was 30%, the R value was 0.60, the Young's modulus was 3.9 MPa, and the maximum point stress was 22.2 MPa.

[0085] [Synthesis Example 2: Synthesis of dilactide / ε-caprolactone copolymer] 50.0g L 36.6 mL of ε-lactide (PURASORB L; manufactured by PURAC Co., Ltd.) as monomers and 0.036 g of octanol as an initiator were placed in a separable flask.

[0086] These were placed under an argon atmosphere, and 0.27 g of the catalyst tin(II) octoate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in 5.8 mL of toluene (ultra-dehydrated) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added, and the reaction was carried out at 140°C and a stirring speed of 100 rpm for 24 hours to obtain a crude polymer.

[0087] The obtained crude polymer was dissolved in 200 mL of chloroform and dropped into 3000 mL of hexane in a stirred state to obtain a precipitate. The precipitate was dried under reduced pressure at 50 ° C for 18 hours to obtain a dilactide / ε-caprolactone copolymer having a gradient structure. The weight average molecular weight of the obtained dilactide / ε-caprolactone copolymer was 200,000, the crystallization rate of the dilactide residue was 0.0%, the crystallization rate of the ε-caprolactone residue was 0.0%, the molar fraction of the dilactide residue was 50%, the molar fraction of the ε-caprolactone residue was 50%, the molar fraction of the structure in which the dilactide residue and the ε-caprolactone residue were adjacent was 43.5%, the R value was 0.87, the Young's modulus was 0.76 MPa, and the maximum point stress was 16.6 MPa.

[0088] [Example 1] The dilactide / ε-caprolactone copolymer obtained in Synthesis Example 1 and poly L A polymer composition solution was prepared by dissolving 10 g of a mixture of dilactide / ε-caprolactone copolymer and polylactic acid (manufactured by Corbion) (weight average molecular weight 180,000) in a mass ratio of 70:30, in 30 mL of chloroform. The results of the evaluation using the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in Figure 1.

[0089] [Comparative Example 1] A polymer solution was prepared by dissolving 10 g of the dilactide / ε-caprolactone copolymer obtained in Synthesis Example 1 in 30 mL of chloroform. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in FIG.

[0090] [Comparative Example 2] A polymer composition solution was prepared in the same manner as in Example 1, except that the mass ratio of the dilactide / ε-caprolactone copolymer to polylactic acid was changed to dilactide / ε-caprolactone copolymer:polylactic acid=50:50. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in FIG.

[0091] [Comparative Example 3] A polymer composition solution was prepared in the same manner as in Example 1, except that the mass ratio of the dilactide / ε-caprolactone copolymer to polylactic acid was changed to dilactide / ε-caprolactone copolymer:polylactic acid=30:70. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in FIG.

[0092] [Comparative Example 4] Poly L A polymer solution was prepared by dissolving 10 g of lactic acid (manufactured by Corbion) in 30 mL of chloroform. The results of the evaluation using the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in Figure 5.

[0093] [Example 2] A polymer composition solution was prepared in the same manner as in Example 1, except that the dilactide / ε-caprolactone copolymer was changed to that obtained in Synthesis Example 2. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in Figure 6.

[0094] [Example 3] A polymer composition solution was prepared in the same manner as in Example 2, except that the ratio of dilactide / ε-caprolactone copolymer to polylactic acid was changed to dilactide / ε-caprolactone copolymer:polylactic acid=60:40. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in FIG.

[0095] [Example 4] A polymer composition solution was prepared in the same manner as in Example 2, except that the ratio of dilactide / ε-caprolactone copolymer to polylactic acid was changed to dilactide / ε-caprolactone copolymer:polylactic acid=80:20. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in FIG.

[0096] [Comparative Example 5] A polymer solution was prepared by dissolving 10 g of the dilactide / ε-caprolactone copolymer obtained in Synthesis Example 2 in 30 mL of chloroform. The results of evaluation by the above-mentioned method are shown in Table 1, and the elongation-stress curve is shown in FIG.

[0097] [Table 1] [Explanation of symbols]

[0098] E: Elongation F: Tensile force (N)

Claims

1. A polymer composition containing polylactic acid and a dilactide / ε-caprolactone copolymer, the polylactic acid being contained in an amount of 20 to 40% by mass relative to 100% by mass of the total of the polylactic acid and the dilactide / ε-caprolactone copolymer, and the dilactide / ε-caprolactone copolymer satisfying the following (1) and (2): (1) The R value represented by the following formula is 0.45 or more and 0.99 or less. R=[AB] / (2[A][B])×100 Here, [A]: Molar fraction (%) of dilactide residues in dilactide / ε-caprolactone copolymer [B]: Molar fraction (%) of ε-caprolactone residues in the dilactide / ε-caprolactone copolymer [AB]: mole fraction (%) of structures (AB and BA) in which a dilactide residue and an ε-caprolactone residue are adjacent to each other in a dilactide / ε-caprolactone copolymer (2) The crystallinity of at least one of the dilactide residues and the ε-caprolactone residues is less than 14%.

2. 2. The polymer composition according to claim 1, wherein the weight average molecular weight of the polylactic acid is 60,000 or more.

3. 3. The polymer composition according to claim 1 or 2, wherein the dilactide / ε-caprolactone copolymer has a structure in which two or more macromer units are linked together, the macromer units having a gradient structure in which dilactide residues and ε-caprolactone residues form a composition gradient in the skeleton.

4. 4. The polymer composition according to claim 1, wherein the dilactide / ε-caprolactone copolymer has a weight average molecular weight of 60,000 or more.

5. A molded article comprising the polymer composition according to any one of claims 1 to 4.

6. The molded article according to claim 5 for use in medical applications.

7. A nerve regeneration-inducing tube, at least in part using the polymer composition according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Implantable drug-eluting medical device

    JP2005525911A

  • Resin composition and its molded article obtained by molding the same

    JP2007138131A

  • Block copolymer, method for producing the same and resin composition

    JP2008037996A

  • Biodegradable polymer film, sheet, wrap and other packaging materials suitable for use as laminate coating

    JP2008255349A

  • Temperature-responsive biodegradable polymer composition and production method thereof

    JP2016190921A